Determinants of climate change adaptation strategies among rural household farmers in the Wolaita zone, Southern Ethiopia - Demissie Dalacho Debisa; Teshome Yirgu Bayu; Thomas Toma Tora (Discover Applied Sciences)
Abstract Climate change poses significant challenges to sustainable development globally, particularly in developing countries like Ethiopia, where agriculture heavily relies on rainfall for livelihoods. This study aimed to examine determinants of climate change adaptation strategies among rural household farmers. A cross-sectional survey was conducted to collect quantitative data from 363 respondents using questionnaires. Additionally, qualitative data were obtained through focus group discussions and key informant interviews. A multi-stage sampling approach was employed to select respondents from farming communities. Data analysis was carried out using a multivariate probit model, a weighted average index (WAI), and a problem confrontation index (PCI). The findings from the multivariate model revealed access to credit, family size, and landholding significantly impact farmers' decisions to adapt to climate change. Moreover, access to information, climate-related knowledge, and education play essential roles in enabling farmers to adopt various adaptation strategies. However, the gender of the household head was found to have no significant effect on adaptation choices. The weighted average index revealed that the leading climate change adaptation strategies include crop diversification (WAI = 2.79), crop rotation (WAI = 2.78), and soil–water management techniques (WAI = 2.69). The problem confrontation index identified major barriers such as high costs of agricultural inputs, insufficient institutional support, and limited market access. Therefore, strong institutional support is essential in helping farming communities overcome these obstacles and enhance their capacity to adapt to climate change effectively.